Technology for Preparation of Chemically Desalted and Softened Water According to Combined Technological Scheme - G. K. Feyziev; M. M. Jalilova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents results of investigations pertaining to developed technological scheme on combined production of chemically desalted and softened water without usage of soda ash for deposition of hardness salt. Scheme application limits in its two operational modes have been determined and mathematical expressions for determination of the main operating conditions have been derived in the paper.